Online Purchase Intention Development Model For Indonesian Millennial Generation - Nasrudin, Inayati; Limakrisna , Nandan; Bahtiar, Usman (International Journal of Applied Management and Business, 2025)
This research aims to identify factors influencing online purchase intention for Indonesian Millennial generation. The methodology used in this research is based on data collection using a questionnaire distributed through Googleform and consisting of 397 respondents. Data processing and analysis have been conducted using Smart PLS. Research resulted: All of the variables Perceived Usefulness, Perceived Self-Efficiency and Overreaction have positive influence on Online Purchase Intention. This research showed that Indonesian millennial generation had emotional rather than rational planning in online purchases. They prefer shopping online rather than offline because they used to proficient to adopt technology as long as technology is easy to use and useful. Based on research results, it is proven that variable overreaction is applied in the stock market for purchasing shares by investors but it is also proven in the consumption market. Indonesian Millennial generation tends to have overreaction on online purchase intention because of big sale, visual appeal, private collection. There are some managerial implications for e-commerce business players, especially to have a strategy to create applications with a more attractive application appearance, offer various promotions, and providing buyer review features. This research has contributed to developing a Technology Acceptance Model with the addition of Perceived Usefulness, Perceived Self-Efficacy and Overreaction variables in online Purchase Intention